Numerical Analysis of the Influence of Block-Stone Embankment Filling Height on the Water, Temperature, and Deformation Distributions of Subgrade in Permafrost Regions - Wei Shan; Min Ma; Ying Guo; Chengcheng Zhang (Water, 2022)
The hydrologic and thermal states of foundation soils have an important influence on subgrade stability in degrading permafrost regions. However, thawing settlement remains a problem in the permafrost regions of Northeast China, because there are few relevant research results in this area, and the foundation deformation mechanism caused by the hydrologic and thermal changes of foundation soils is not clear. Therefore, a subgrade structure with large block stones as embankment filler was proposed to improve the foundation thawing settlement, and it has been successfully implemented in the road project (Yiershi–Chaiqiao section of 308 Provincial Highway) in Inner Mongolia Autonomous Region. To study the action mechanism of this structure on the subgrade deformation, a numerical model of the hydro–thermal–mechanical interaction process in unsaturated frozen soil was established, and the calculation of the water content, temperature, and deformation conditions of the subgrade within 20 years of the highway were carried out. The results show that the embankment block-stone layer can reduce the total heat of the deep foundation, and reduce the migration of unfrozen water from the deep foundation to the active layer. It can also increase the hydrologic and thermal convective flux inside and outside the block-stone layer, thus raising the permafrost table and reducing the subgrade deformation. The block-stone layer thickness has an important influence on the subgrade stability. By comparing the hydrologic, thermal change, and deformation of the block-stone structures with different thicknesses (5.0 m, 4.0 m, 3.5 m, 3.0 m, and 2.0 m), we found that when the thickness of the block-stone layer is 4.0 m, the subgrade stability is the best. In this case, the maximum uneven settlement and the maximum transverse deformation difference of the top surface of the subgrade are +0.521 cm and +0.462 cm, respectively. The subgrade stability is less optimal when the block-stone layer thickness is greater or less than 4.0 m. Thus, ...